(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study offers a succinct summary of leadership lessons that may be drawn from the characters of Ramayana. The Ramayana, one of the most renowned epics, is regarded as a magnificent work of literature and the first to be created in an Indian context. The Indian scriptures contain significant insight that can be utilized for modern administrative and leadership techniques. Several chapters in Scripture contain a wealth of wisdom that highlights important ideas and principles important to good management and leadership. The global application of these lessons is contributing to the resolution of current business issues. Further, these concepts cut across historical and cultural barriers, providing insightful guidance for leaders in various organizational circumstances. Nevertheless, there is a dearth of research on the topic of Ramayana and the leadership. Because of this, authors have realized that in order to lead successfully they must comprehend how great ideas and lessons can be applied to the development of management practices.